A Central Role for Atg5 in Microbiota-Dependent Foxp3+ RORγt+ Treg Cell Preservation to Maintain Intestinal Immune Homeostasis - Plaza-Sirvent, Carlos; Zhao, Bei; Bronietzki, Alisha W.; Pils, Marina C.; Tafrishi, Neda; Schuster, Marc; Strowig, Till; Schmitz, Ingo (Frontiers in Immunology, 2021)
Autophagy is an evolutionary conserved catabolic pathway that ensures the degradation of intracellular components. The autophagic pathway is regulated by autophagy-related (Atg) proteins that govern formation of double-membraned vesicles called autophagosomes. Autophagy deficiency in regulatory T (Treg) cells leads to increased apoptosis of these cells and to the development of autoimmune disorders, predominantly characterized by intestinal inflammation. Recently, RORgt-expressing Treg cells have been identified as key regulators of gut homeostasis, preventing intestinal immunopathology. To study the role of autophagy in RORgt+ Foxp3+ Treg cells, we generated mice lacking the essential component of the core autophagy machinery Atg5 in Foxp3+ cells. Atg5 deficiency in Treg cells led to a predominantly intestinal inflammation. While Atg5-deficient Treg cells were reduced in peripheral lymphoid organs, the intestinal RORgt+ Foxp3+ subpopulation of Treg cells was most severely affected. Our data indicated that autophagy is essential to maintain the intestinal RORgt+ Foxp3+ Treg population, thereby protecting the mice from gut inflammatory disorders.